Transparency, access and re-use of information in the context of public sector digital transformation: lessons and challenges in the age of COVID-19 - Valero Torrijos, Julián; Cerdá Meseguer, Juan Ignacio (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
Digital transformation of public sector involves a firm commitment to innovation and, particularly, to the true integration of information systems based on open data, transparency and PSI re-use standards. In this respect, sincere inter-administrative collaboration, effective use of the innovation possibilities of technology, a decided support for the principles of Open Government, the cooperation with the private sector and the overcoming of an information management model largely constrained by an out-of-focus understanding of the data protection legislation are some of the main actions to be promoted. As it has been shown over the past few months in the fight against the COVID-19 pandemic, it is becoming urgent to design a new model of information governance in order to tackle this challenge.
Keywords: Open Government; digital transformation; data protection & PSI re-use; digital public services co-creation; personal data protection; health data; COVID-19